Exploring the Relationship Between Gadget Use and Learning Focus Among Children with ADHD in Inclusive Schools - Elvira Asril; Zamzami Zamzami; Yogi Yunefri; Rizki Novendra; Yogo Turnandes (STAI Hubbulwathan Duri, 2025)
Children with Attention Deficit Hyperactivity Disorder (ADHD) often struggle to maintain focus, leading to low participation and poor academic outcomes. While gadgets are frequently viewed as distractions, they also offer potential as interactive learning tools. This study investigates the relationship between gadget use and learning focus among children with ADHD in inclusive schools. A quantitative survey with a correlational design was employed. Two variables were measured: gadget use as a learning medium (X) and the learning focus of children with ADHD (Y). Data were collected from 50 respondents, including classroom teachers, special assistant teachers (GPK), and therapists experienced in supporting children with ADHD using gadgets. A Likert-scale questionnaire was tested for validity and reliability, and data were analyzed using Pearson correlation and regression analysis. Findings showed that gadget use among respondents was relatively high (mean = 39.94). However, correlation analysis indicated no significant relationship between gadget use and learning focus (r = –0.12, p 0.05). Regression analysis suggested that increased gadget use did not predict improvements in attention, and in some cases showed a negative trend. These results highlight that high gadget usage alone does not enhance learning focus in children with ADHD. The effectiveness of gadgets depends on structured pedagogical frameworks, appropriate application design, and alignment with learners’ characteristics. Gadgets can support ADHD learning only when integrated with tailored instructional strategies. Future research should explore specific app features and teaching models to optimize their educational benefits.